Notes on biliary infections. Changing criteria - del Campo, Juan C (Cirugía del Uruguay, 2020)
The changeable judgement in stimating the significance of the infection in biliary pathology are analyzed. The commonly secondary ( as consecutive) role of the infection in acute cholecystitis, is emphasized. The results of biliary infection treatment have been improved by antibiotic therapy, but: 1) it may be inoperating on a -closed focus ( obstrucive holecystitis) ; 2) it may alter the bacteria! flora. Recently, the author has observed severa! cases where he has not found but pseudomona aeruginosa or proteus. Finally, the difficulty in performing a diagnosis of non-obstructive forms of biliary infection, is emphasized.